-3(m-7)=2m-4

Simple and best practice solution for -3(m-7)=2m-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(m-7)=2m-4 equation:


Simplifying
-3(m + -7) = 2m + -4

Reorder the terms:
-3(-7 + m) = 2m + -4
(-7 * -3 + m * -3) = 2m + -4
(21 + -3m) = 2m + -4

Reorder the terms:
21 + -3m = -4 + 2m

Solving
21 + -3m = -4 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
21 + -3m + -2m = -4 + 2m + -2m

Combine like terms: -3m + -2m = -5m
21 + -5m = -4 + 2m + -2m

Combine like terms: 2m + -2m = 0
21 + -5m = -4 + 0
21 + -5m = -4

Add '-21' to each side of the equation.
21 + -21 + -5m = -4 + -21

Combine like terms: 21 + -21 = 0
0 + -5m = -4 + -21
-5m = -4 + -21

Combine like terms: -4 + -21 = -25
-5m = -25

Divide each side by '-5'.
m = 5

Simplifying
m = 5

See similar equations:

| 7x+2+2+3+8=180 | | -3x=x-20 | | 3x+5y=328 | | (-9)=b+(-13) | | 13=-6+2x | | 4u-8=5(4-u)-1 | | 13=6-2x | | A-4=(-5) | | 10y-2x=50 | | 6x+12+2x+60=90 | | -12.7+-4.4=x | | K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 |

Equations solver categories